The impact of oral health disparities on smoking prevalence - Carneiro, Pedro Henrique; Zhang, Alice; Zhao, William; Ojcius, David M.; Daly, Ladan; Almeida-da-Silva, Cassio Luiz Coutinho (Frontiers in Public Health, 2025)
Smoking increases the risk of heart disease, cancer, lung infections, and diabetes, and causes oral health problems. The prevalence of smoking is significantly influenced by intersecting factors such as socioeconomic status, racial and ethnic marginalization, and differing cultural practices. Importantly, minority groups experience earlier tobacco exposure and reduced access to education and cessation programs. A comprehensive analysis of individual characteristics is essential for predicting and effectively addressing tobacco-related oral and systemic health disparities. Education and prevention initiatives are key to decreasing the prevalence of smoking in populations affected by structural inequities.